THE EFFECT OF TWO STAY-TWO STRAY METHOD ON THE SPEAKING ABILITY OF THE FIRST YEAR STUDENTS OF SMK TELKOM PEKANBARU - Poppy Meilani Rizki; Fadly Azhar; Dahnilsyah Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research aimed to discover the effect of Two Stay-Two Stray (TSTS) Method on the speaking ability of the first year students of SMK Telkom Pekanbaru academic year 2018/2019. The selected sample was X TKJ-2 students which consisted of 34 students. The sample was selected by using cluster random sampling technique. This research was pre-experimental and the data were collected by means of pre-test and post-test design in the form of speaking test which focused on describing objects. The data were analyzed using five components of speaking: pronunciation, grammar, vocabulary, fluency, and comprehension. The results showed that the score of the pretest was 60.47, the post-test was 72.98 while the improvement from both scores was 12.51. Therefore, it can be concluded that there is a significant effect of TSTS Method on the speaking ability of the first year students of SMK Telkom Pekanbaru. In other words, the teaching of speaking by through Two Stay-Two Stray Method, as one of the alternative speaking activities, has an effect on the students’ speaking ability.Keywords: Two Stay-Two Stray Method, Speaking Ability